CHALLENGES OF INDONESIAN TEACHER COMPETENCE IN DEALING WITH ASEAN ECONOMIC COMMUNITY (AEC) - Meita Lesmiyati Khasyar (JELLi Journal, 2021)
This article examines the professional competence of teachers in the face of the MEA. The method in this paper describes a problem that there is in the competence of teachers in Indonesia in the face of the MEA. MEA is a form of realization of the ultimate goal of economic integration in Southeast Asia. In 2015 an agreement ASEAN Economic Community (AEC) or the ASEAN Economic Market comes into force. This agreement not only have an impact on the economic sector, but also in other sectors. No exception "education" as the capital to build competitive human resources. MEA challenges in education that will face, among others, the proliferation of foreign educational institutions, educational standards and orientation of the increasingly pro-market, as well as the labor market is flooded with foreign workers. For the ASEAN free trade era, to be greeted by the world of education quickly, so that Indonesian human resources ready to face the tight competition with other countries. Competence of teachers and the quality of educational institutions, thus becoming an absolute necessity as well as well as a password or key words to give birth to sons and daughters of the civilized, productive, creative, innovative and effective. Joy and hope of civilized human birth mentioned above should have been born of an educational institution that a national standard (IPNS) and even internationally